Successful and effective managers : a comparison between American organisations and a New Zealand organisation : a research report presented in partial fulfilment of the requirements for the degree of Master of Business Studies at Massey University - Chalmers, Lesley Rachel (Massey University, 1991)
In this report the issue of successful and effective management styles will be examined within a New Zealand context and compared with results obtained from American Organisations. Recent American research indicates that most managers who are promoted quickly (successful) are not the ones who achieve outstanding results at work (effective). Similarly it appears that in the American Organisations studied, the most effective managers do not receive recognition in the form of promotion. In the majority of management literature the terms successful and effective have been used interchangeably. Research undertaken by the American academic Fred Luthans suggests that the two areas are quite distinct from one another and in fact few managers are both successful and effective. Luthans identifies in his research the duties/tasks undertaken by successful managers and by effective managers, the differences in these areas are significant.
Keywords: Executives; New Zealand; United States